Performance of phalaenopsis orchids under varying shade levels - Pavithra C G (Department of Pomology and Floriculture, College of Agriculture, 2008)
Orchids, the most beautiful flowers in god's creation, belongs to the family Orchidaceae. Phalaenopsis called the 'Moth Orchids' are recognised as the most beautiful flowers among orchids. Their long arching sprays of long lasting blooms are very popular throughout the world. One of the critical factors identified for successful growing of orchids is light. Determining the most suitable shade level for early vegetative growth of orchids is important as it influences the pre-flowering period, flower induction and flower production. The present work was thus taken up with a view to assess the performance of three Phalaenopsis cultivars under varying shade levels and to determine the most suitable shade level for early vegetative growth of hardened plants. The experiment was carried out at the Department of Pomology and Floriculture , College of Agriculture, Vellayani during 2006 -2007 with a view to assess the performance of Phalaenopsis orchids under varying shade levels and to determine the most suitable shade level for early vegetative growth of hardened plants. The following three commercially grown cultivars of Phalaenopsis orchids were used as the experimental material. The cultivars are Phalaenopsis Hsin, Phalaenopsis Luchia Pink and Phalaenopsis Brother Girl. For the three experiments, shade was provided with black high density polyethylene shade net calibrated for 25 %, 50 % and 75 % shade. Effect of shade and cultivar differences influenced the plant growth, shoot and leaf morphology and physiological and anatomical characteristics of the hardened plants. Among the cultivars, Phalaenopsis Hsin was found to be the best cultivar for obtaining greater number of roots, shoot length, shoot girth, internodal length, length and width of the leaves. Phalaenopsis Brother Girl was found to be the best cultivar for maximum leaf thickness and number of stomata on upper and lower surface of the leaves. Phalaenopsis Luchia Pink was found to be the best cultivar for greater root length and root thickness. The most suitable shade level conducive for shoot length, shoot girth, number of leaves, length and width of the leaves was found to be 50%. The most suitable shade level for greater number of roots, root thickness, thickness of leaves and chlorophyll (b) leaves was found to be 25% The interaction between shade and cultivar differences were also found to influence the performance of hardened plants.